Free-running CFD simulations to assess a ship-manoeuvring control method with motion forecast in waves. (1st March 2023) - Kim, In-Tae; Kim, Sanghyun; Paik, Kwang-Jun; Yang, Jung-Kyu; Kwon, Soo-Yeon
Abstract: In this study, Computational Fluid Dynamics (CFD) based free running simulations of a tanker model were performed to assess a ship-manoeuvring control method with motion forecasting in waves. A modified Time-Varying Auto-Regressive (TVAR) model was developed as a forecast model for predicting the changes in the heading angle. Furthermore, Functional Mock-up Unit (FMU) was developed and embedded in the CFD model to perform the steering operation based on the predicted heading angle. The results confirmed that the motion-forecasting control method improves the course keeping and course changing performance, showing faster heading change, decreased heading overshoot and reduced rudder manipulation. Highlights: Free running CFD simulations were performed to assess the rudder control methods with and without the motion forecasting in waves. The forecast-based control method utilise the forecasted yaw motion as a control input. The CFD simulations were performed under two different manoeuvre modes, weathervaning and course keeping modes. The forecast-based method showed better course changing and keeping performances compared to the present-based method.